Criminal Trial and Investigation Vol. 1 - P C Banergee (Gurgaon Thomson Reuters, 2016)
Criminal Trial and Investigation by P.C. Banerjee is an odyssey towards Justice and is meant for doing Justice not only to the victim but also to the society at large. Criminal Trial is a process for doing Public Justice by punishing the criminal. A judge does not preside over a Criminal Trial merely to see that no innocent man is punished but also presides to see that a guilty man does not escape. Ipso facto, both are public duties.
Includes Index.
English
Keywords: Criminal Law; Law